Case report: Traumatic lumbosacral spondyloptosis with locked L5 inferior articular process - Tang, Tao; Liu, Yuchi; Cao, Jian; Wu, Tianlong; He, Dingwen; Cheng, Xigao; Xie, Shuihua (Frontiers in Surgery, 2023)
Abstract Background: Traumatic lumbosacral spondyloptosis is a very rare spinal disease caused by high-energy trauma. We report a case of traumatic lumbosacral spondyloptosis with locked L5 inferior articular process. Case presentation: A 33-year-old man presented with multiple pain for 6 hours following waist trauma and was admitted to the hospital. He suffered multiple injuries from severe impact on the waist because driving the forklift truck was out of control. The preoperative imaging examinations revealed that the patient was diagnosed with traumatic lumbosacral spondyloptosis and the L5 inferior articular process was locked into the anterior margin of the S1 vertebra. A posterior instrumentation, decompression of the cauda equina and interbody fusion procedure was performed. The patient received hyperbaric oxygen and rehabilitation treatment 10 days after the surgery. At the 6-month follow-up postoperatively, the muscle strength of the lower limbs was improved, the patient had no numbness of both lower limbs, and the symptom of urinary retention was significantly improved. The ASIA grade was from grade C preoperatively improved to grade D postoperatively. As far as we know, there have been no relevant reports on traumatic lumbosacral spondyloptosis with locked L5 inferior articular process yet. Conclusion: We believe that the hyperflexion and shear forces were the potential causes of this injury. Iin addition, the preoperative imaging examinations should be evaluated carefully. If the inferior articular process of L5 were locked, we suggest to remove the bilateral inferior articular processes first, and then perform reduction.